Digital technology for social contact: A descriptive study of older adults` experiences with KOMP - Berg, Anita; Myren, Gunn Eva Solum (Nordisk Tidsskrift for Helseforskning, 2021)
This study describes older adults’ experiences with use of KOMP, a digital technology for social contact developed to reduce involuntary loneliness and social isolation. Empirically, the study is based on interviews with six older adults still living at home. By reflexive thematic analysis, the findings are grouped into four themes: Dependence on others will and initiative, Increased social connectedness to family, Control and security and Impulses and activity in everyday life. The study shows that the experiences with KOMP generally is positive, context-dependent and multidimensional. KOMP is a technology without content, and experiences depend on whether and how the KOMP application is used by those who are connected to the KOMP network. Furthermore, the study shows that the participants' experiences are related to the intended functions embedded in KOMP, and unintended functions enabled by KOMP.
Keywords: Older adults; social connectedness; information and communication technologies; KOMP; qualitative research; reflexive thematic analysis